Impact of Trump Tariffs on Global Trade, GDP and Employment: An Analysis - Kanupriya, Kanupriya (Theoretical and Practical Research in Economic Fields; Vol 16 No 4 (2025): TPREF Special Issue, Volume XVI, Issue 4(36), Winter 2025, 2025)
With Trump’s return to the White House in 2025, many expected that he would fulfill his campaign promise to impose tariffs on alleged unfair participants within the global trade system. On April 2, 2025, also known as ‘Liberation Day’, he acted on his poll promise by significantly increasing tariffs (or reciprocal tariffs) on most of the United States’ trade partners, which resulted in market turmoil and pushed businesses into a prolonged period of uncertainty. Understanding the macroeconomic implications of Trump’s tariffs, as well as any potential long-term effects, could help the world manage these challenges effectively. Given this situation, it is crucial to continuously assess the impact on the global economy, especially on world trade, GDP and employment. This article seeks to assess the impact of ‘Trump Tariffs’ on the following global macroeconomic variables - world trade, global GDP and global employment using quantitative and qualitative analyses comprising review of existing literature on the topic, trends for the variables of interest and simple time series analysis for the period 1990 to 2025. In this dynamic landscape (Trump had suspended the implementation of his reciprocal tariffs in April 2025 itself), stakeholders must move away from rigid strategies and instead develop flexible, analytical skills to navigate this tumultuous new environment. All in all, this article reiterates the virtue of free trade over protectionist policies.